COVID-19 Vaccine Policy as an Effort to Achieve National Herd Immunity in Indonesia - Henny Juliani, Kadek Cahya Susila Wibawa, Solechan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The rapid and extensive spread of COVID-19 has increased the number of confirmed cases even higher. The COVID-19 vaccine policy is one strategy for reducing COVID-19 spread by establishing a joint herd immunity pattern. The vaccine policy is one of the policies, along with the 3M and 3T policies. Objectives: This paper aimed to analyze the implementation of the COVID-19 vaccination policy to achieve herd immunity. Research Methodology: This research uses a normative method (qualitative) and descriptive-analytical (research specification). The choice of this method is based on the fact that this research examines the government’s policies and their impact on the achievement of national herd immunity. Conclusion: This study found that the COVID-19 vaccine policy was effective in encouraging people to get vaccinated immediately. The COVID-19 vaccine policy has achieved 94.71 percent coverage for dose I, 77.30 percent coverage for dose II, and 12.63 percent coverage for dose III. Herd immunity can be achieved if at least 70% of Indonesians have been vaccinated.